THE VENTURE CAPITAL: IT'S A WAY OF FINANCING THE INNOVATIVE START-UPS - EL HSSINI , Soufiane; BENTAHAR , Mohammed (Revue du contrôle, de la comptabilité et de l’audit, 2020)
The offer of financing on the Moroccan financial market is insufficient, and that some start-ups consider external financing as a brake on their development, either because they can not access it, or because the conditions of obtaining are considered unreasonable, so we must discover elsewhere the origin of the problem. Start from discussions with young entrepreneurs, researchers, funders and bankers have led us to a common point of the problem, the identification of the risk assessment related to innovation projects. So the financing of start-ups and their innovation projects remains a problematic.